Genome Size and Sex Chromosome Variability of Bed Bugs Feeding on Animal Hosts Compared to Cimex lectularius Parasitizing Human (Heteroptera: Cimicidae) - Sadílek, David; Urfus, Tomáš; Vilímová, Jitka (Cytometry. Part A, 2019)
Genome size and chromosome number of five Cimicidae species were compared with the similar data recently received from Cimex lectularius parasitizing human. The average nuclear DNA content (males) was 2C = 1.47 pg in C. hemipterus, 2C = 1.61 pg in C. hirundinis, 2C = 1.80 pg in C. lectularius from bats, 2C = 1.68 pg in C. pipistrelli, and 2C = 1.22 pg in Paracimex cf. chaeturus. In the genomes of all cimicid species analyzed, the average GC content ranged from 32.74% in C. pipistrelli to 35.87% in P. cf. chaeturus. Chromosome variability with two male cytotypes, 2n = 28 + X1 X2 Y and 28 + X1 X2 X3 Y, was confirmed in C. pipistrelli. In addition, intraspecific variability in chromosome number was revealed in C. lectularius from bats with 2n = 26 + X1 X2 Y and 26 + X1 X2 X3 Y. We suggest that the origin of intraspecific variability in chromosome number of C. lectularius from bats and C. pipistrelli is not only the result of simple fragmentation, but additive rearrangements like duplications are probably also involved. © 2019 International Society for Advancement of Cytometry.
Keywords: Bedbugs; fragmentace DNA; Chiroptera; štěnice; zárodečné buňky; ploidie; Sex Chromosomes; délka genomu; zvířata; lidé; ženské pohlaví; buněčné jádro; cytogenetické vyšetření; Gonads; zastoupení bazí; průtoková cytometrie; Germ Cells; Cytogenetic Analysis; chromozomy; Female; mužské pohlaví; Flow Cytometry; Chromosomes; Cell Nucleus; Genome Size; Base Composition; DNA Fragmentation; Humans; Ploidies; Animals; Male; pohlavní chromozomy; gonády